Asymmetric hetero-diels–alder reaction of Danishefsky’s dienes with α-carbonyl esters catalyzed by an indium(III)–PyBox complex - Zhao, Bei (2013)
An efficient catalytic enantioselective hetero-Diels–Alder reaction of Danishefsky’s dienes with α-carbonyl esters using a chiral In(III)–pybox complex has been demonstrated. This protocol offers several advantages, including mild reaction conditions, relatively low catalyst loading, and good to excellent enantioselectivities. Furthermore, the absolute configurations of the new alkynyl-containing products were determined by CD spectra in combination with TD-DFT calculations.